Saintis dan Al-Quran: Kontribusi Saintis Indonesia dalam Kajian Quran di Masa Modern - Firmansyah, Rizki; Erik Tauvani Somae; Budi Jaya Putra; Efrita Norman (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Those adherents of liberalism and religious secularism should not enter into personal affairs, it should not be mixed with the study of science at all. People like Karl Mark, Durheim, and Weber became his reference, they all agreed to marginalize religion from modern life. The separation of religion and science seems to be a necessity that is currently inherited and applied in scientific life massively. But now, in today's civilization, the separation between religion and science is considered a mistake. They realize it even though they are still shy about admitting it, in Islam itself, there is no postulate that science is separated from religious science because for Islam the origin of the two is one, that is, the creator. This is what underlies some scientists to see religion with the effectiveness of science and vice versa. In Indonesia, especially some scientists with different backgrounds try to see the Quran from the perspective of scientists they have and try to present the Quran with a logical and rational view to grow and strengthen the faith. This research is qualitative research with analysis texts approach, the primary source of this study is the work of Indonesian scientists and their study of the Quran, and the data taken comes from literature reviews. The results of this study state that even the study of religion and science is not contradictory and appropriate in modern civilization today.